ANALISIS MENGENAI KEMAMPUAN SUATU DAERAH DALAM PENYEDIAAN PANGAN DI JAWATENGAH - ENY Hari Widowati (JURNAL LITBANG PROVINSI JAWA TENGAH, 2005)
This research is done in library research using data of centraljava agriculture production from 2000 to 2004, with objects: rice, com, soybean and cassava. Quality method was used to classify the ability of the area in producing food and the ability of the area in providing food. The result of the analyses recommended several aspects: (I) Intensification and extensification should be done in order to fulfill the supply needs for rice, com, soybean and cassava; (2) Government should in· crease the farmer awareness to plant soybean by intensification methods to maximize the products; (3) Government should import from the productive areas to the food shortage areas in order to fulfill the needs for rice, com, soybean and cassava